Learning Style Profiles and Adaptive Teaching Needs in EFL Higher Education: A Felder–Silverman-Based Mixed-Methods Study - Nurlaila Husain; Moon H. Otoluwa; Rasuna R. Talib; Salam Salam (Randwick International of Education and Linguistics Science Journal, 2026)
This study investigates the learning style profiles of EFL undergraduate students and the relationship between these profiles and the necessity of adaptive teaching in higher education. The study builds on the understanding that students respond differently to instructional input, while classroom teaching continues to be delivered through a fairly homogenous approach. This study used the Felder–Silverman Learning Style Model as the analytical framework to identify students’ learning style tendencies and to analyse the perceptions of the lecturers and students on the need of adaptive teaching. To gain a broader understanding of the issue, a convergent mix-methods design was employed. Quantitative data were collected from 98 students, using the Index of Learning Styles and an adaptive teaching needs questionnaire. 11 lecturers filled in a similar needs questionnaire. Qualitative data were gathered through structured interviews with selected lecturers and students. The questionnaire data were analyzed using descriptive statistics, whereas the interview data were examined thematically and integrated during the interpretation stage. The findings revealed that active, sensing, visual, and sequential tendencies were the most dominant among the students. However, the presence of reflective, intuitive, verbal, and global learners indicates that instruction should remain flexible and varied rather than being guided by fixed learning-style labels. Both lecturers and students reported strong needs for adaptive teaching, especially in relation to learner profile data, varied instructional strategies, multimodal resources, flexible learning activities, adaptive assessment, remedial support, and enrichment. The study concludes that learning style profiles are most useful as diagnostic information for supporting inclusive, responsive, and adaptable EFL instruction.